2014
DOI: 10.1063/1.4890501
|View full text |Cite
|
Sign up to set email alerts
|

Keto-enol tautomerization and intermolecular proton transfer in photoionized cyclopentanone dimer in the gas phase

Abstract: Time-of-flight mass spectra of cyclopentanone and its clusters cooled in a supersonic jet expansion have been measured following 4-, 3-, and 2-photon ionizations by the 2nd, 3rd, and 4th harmonic wavelengths, respectively, of a Q-switched Nd:YAG laser. The mass spectra reveal signatures of energetically favored keto to enol tautomerization of the molecular ion leading to intermolecular proton transfer, and this observation is found sharply dependent on the ionization wavelengths used. Electronic structure calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…There are numerous examples in the literature of isomeric effects on electronic excited state dynamics 9 and on the relative production of fragment ions in mass spectrometry experiments. 46 Therefore, the plausibility of this attribution depends primarily on the idea that the relative populations of different uridine isomers can change significantly as a function of the desorption laser power (and hence foil temperature) in the present experiments. The calculations in Section 3 show that conformational isomeric transitions of uridine can occur at much lower temperatures than decomposition, and a range of higher barriers have been reported for different isomeric transitions in the literature.…”
Section: Resultsmentioning
confidence: 88%
“…There are numerous examples in the literature of isomeric effects on electronic excited state dynamics 9 and on the relative production of fragment ions in mass spectrometry experiments. 46 Therefore, the plausibility of this attribution depends primarily on the idea that the relative populations of different uridine isomers can change significantly as a function of the desorption laser power (and hence foil temperature) in the present experiments. The calculations in Section 3 show that conformational isomeric transitions of uridine can occur at much lower temperatures than decomposition, and a range of higher barriers have been reported for different isomeric transitions in the literature.…”
Section: Resultsmentioning
confidence: 88%
“…47 In one of our previous studies we have shown the occurrence of IMPT in the photoionized jetcooled dimeric complex of a small cyclic ketone, cyclopentanone. 50 In that case, the enol form was found to be more stable in the cationic ground state, and the energy barrier for keto to enol conversion was shown to reduce drastically in the hydrogen bonded dimeric adduct. Recently, an almost barrierless IMPT was claimed to be occurring in the dimeric complex of acetaldehyde, upon 1-photon VUV ionization, and the same was corroborated also by means of electronic structure theory methods.…”
Section: Introductionmentioning
confidence: 97%
“…There are also some important developments regarding the characterization of tautomerisation processes and particularly transition states [12][13][14]. Apart from single molecules, the size of the clusters and their respective structures play an important role in determining the tautomerisation process [15] in those cases.…”
Section: Introductionmentioning
confidence: 99%